2015
DOI: 10.1177/0300060514566649
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis comparing doublet and single cytotoxic agent therapy as first-line treatment in elderly patients with advanced nonsmall-cell lung cancer

Abstract: Objective: To perform a systematic review and meta-analysis comparing doublet versus single agent therapy in elderly patients with advanced nonsmall-cell lung cancer (NSCLC). Methods: PubMed Õ and Cochrane databases, and American Society of Clinical Oncology, World Congress of Lung Cancer, and European Society of Medical Oncology abstracts were searched. Endpoints were overall survival (OS), 1-year survival rate (1-year SR), overall response rate (ORR), and grade 3/4 adverse events. Subgroup analyses were base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Specifically, vinorelbine, a semi-synthetic vinca alkaloid, exhibits anti-cancer properties, especially against advanced NSCLC [ 14–16 ]. Carboplatin, part of the platinum-based anti-cancer drug family, is considered standard care for advanced NSCLC when used in combination therapies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, vinorelbine, a semi-synthetic vinca alkaloid, exhibits anti-cancer properties, especially against advanced NSCLC [ 14–16 ]. Carboplatin, part of the platinum-based anti-cancer drug family, is considered standard care for advanced NSCLC when used in combination therapies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this same meta-analysis, these investigators reported that non-platinum-based doublet therapy offered no survival advantage over single agent therapy (HR = 0.93; 95% CI = (0.86, 1.01); p =0.078), thus further showing the importance of platinum-based chemotherapy in older non-small cell lung cancer patients. [2] This trade-off of modest survival in exchange for increased toxicity suggests a need to further study platinum-based doublet chemotherapy in the first-line setting in older non-small cell lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%